(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
This article offers a comprehensive philosophical examination of the concept of the Perfect Human Being (al-insān al-kāmil), which occupies a central position in Sufi philosophy. The study is grounded in the works of Mahmud Shabistari, Ibn al-ʿArabi, and ʿAziz al-Din Nasafi [1–4]. Within this framework, the Perfect Human Being is interpreted as the ontological telos of existence and as the most complete manifestation of the divine names and attributes. The paper also explores the epistemological scope of this concept, its aesthetic dimensions, and the problem of knowledge as articulated through the symbolic notion of “light.”